Synthesis of the first radiolabeled 188Re N‐heterocyclic carbene complex and initial studies on its potential use in radiopharmaceutical applications. (29th May 2014) - Wagner, Thomas; Zeglis, Brian M.; Groveman, Sam; Hille, Claudia; Pöthig, Alexander; Francesconi, Lynn C.; Herrmann, Wolfgang A.; Kühn, Fritz E.; Reiner, Thomas
<x xml:space="preserve">Abstract</x> A novel approach towards the synthesis of radiolabeled organometallic rhenium complexes is presented. We successfully synthesized and analyzed the first 188Re‐labeled N‐heterocyclic biscarbene complex, trans‐dioxobis(1, 1′‐methylene‐bis(3, 3′‐diisopropylimidazolium‐2‐ylidene))188rhenium(V) hexafluorophosphate (188Re‐4) via transmetalation using an air‐stable and moisture‐stable silver(I) biscarbene complex. In order to assess the viability of this complex as a potential lead structure for in vivo applications, the stability of the 188Re‐NHC complex was tested in physiologically relevant media. Ultimately, our studies illustrate that the complex we synthesized dissociates rapidly and is therefore unsuitable for use in radiopharmaceuticals. However, it is clear that the transmetalation approach we have developed is a rapid, robust, and mild method for the synthesis of new 188Re‐labeled carbene complexes. Copyright © 2014 John Wiley & Sons, Ltd.